Transmission System Power Flow Model - Lukac, Michal; Brumercik, Frantisek; Krzywonos, Leszek; Krzysiak, Zbigniew (Communications - Scientific letters of the University of Zilina, 2017)
Physical modelling of transportation system is helpful for finding information about the power flow in particular transmission elements. The vehicle power train model can be built from predefined blocks. The blocks are based on mathematical equations, which define every power train element. The procedure of the particular transmission element – a two-stage epicyclic gearbox model creation and calculation is described in the presented article.